Harmony in Schools: Exploring the Impact of the Peaceful Schools Program in Building Tolerance and Peace - Munandar, Siswoyo Aris; Fahrurrozi, Fahrurrozi (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
This research explores the implementation and impact of the Peaceful School Program managed by the Wahid Foundation in several Senior High Schools (SMA) in Indonesia. The research method used is a qualitative descriptive case study approach, with a focus on an in-depth understanding of how this program is implemented in specific schools and how it impacts students, teachers and the school environment as a whole. The results of this research reveal how the Peaceful Schools Program has created a more inclusive educational environment and encouraged a better understanding of the values ​​of tolerance, peace and inclusion among students. Yenny Wahid as Director of the Wahid Foundation, the Peaceful Schools Program is an initiative that was born in response to the results of a survey on socio-religious tolerance trends conducted by the Wahid Foundation in 2016. In 2018, the Wahid Foundation reported that the Peaceful Schools program had been implemented in several high schools/vocational schools in provinces such as DKI Jakarta, West Java, East Java and Central Java. In Central Java Province, there are already 5 schools implementing the Peace School program, namely SMAN 7 Semarang, SMAN 10 Semarang, SMAN 11 Semarang, SMAN 13 Semarang, and SMAN 1 Cepiring Kendal. To date, the Peace School has been implemented in 79 Senior High and Vocational Schools (SMA/SMK) in the region. Good cooperation between Indonesia and Australia, through AIPJ2, has contributed to the success of the Peaceful Schools initiative in promoting tolerance and peace in the educational context in Indonesia.